PENGARUH UKURAN PERUSAHAAN DAN PERGANTIAN AUDITOR TERHADAP NILAI PERUSAHAAN DENGAN AUDIT DELAY SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN MANUFAKTUR DI BEI - Patria, Andika; Lestari, Siti; Maulana, Arief Rio (POLITEKNIK LP3I JAKARTA, 2025)
This study is conducted to explore and evaluate the influence of company size and the auditor switching on company value, as well as to assess the mediating role of audit delay in the relationship between coompany size, auditor switching, and company value. The reasearch sample includes 15 manufacturing companies on IDX during the 2021-2023 period that experienced delays in financial reporting. The analysis is performed using a variance based SEM-PLS approach. In this research, udit delay refers to dellay exceeding 90 days. The finding reveall that company size and auditor switching do not significantly impact company value. Furthermore, audit delay is found to mediate the relationship between company size and company value, while it does not mediate the effect of auditor switching on company value.